Freedom of Speech on Children’s Right Setting Toward Prevention of Bullying in Early Childhood Education: A Literature Review of Decolonization Approach - Insan Sheny Priyandita; Mubiar Agustin (IJORER : International Journal of Recent Educational Research, 2021)
The discourse on freedom of speech, in particular when expressing an opinion on the provisions of the Rights of the Child, is often ignored by a trend of change in education that is too concentrated on the authoritarian educational process that prioritizes the success of academic learning rather than the socio-emotional success of children. It is important to communicate the experiences and feelings experienced by children, particularly bullying that occurs early in childhood. This research would examine the importance of free expression in children's rights to the prevention of bullying in early childhood through a decolonization approach. This study employed a literature review approach with a transformative paradigm which take a look at critical thoughts about children's rights, particularly freedom of speech that aims at preventing the bullying that occurs in early childhood. This study argued that the process of preventing bullying and even other negative behavior is effective when parents and teacher properly enforce the rights of children, especially freedom of speech. These results further illuminate the complexities faced by teachers in the application of free expression in early childhood education in daily life.